Placenta humana como modelo de treinamento para cirurgias de aneurismas cerebrais - Jose Augusto Malheiros dos Santos Filho (2015)
Neurosurgery is a demanding specialty that involves many microsurgical procedures with complex skills, including open surgical treatment of intracranial aneurysms. Surgical simulators may be useful for acquiring these skills before trainees perform surgery on human patients. Among several models human placenta is one of the best choices. OBJECTIVE: 1) identify and measure the human placenta vessels to correlate with main brain arteries. 2) describe a human placenta model for the creation and clipping of brain aneurysms. METHODS: First part: 10 human placentas were prepared for its vessels measurement and correlation with brain vessels. Normal saline was injected into the placenta vein and two arteries with flow pressure between 70 and 90mmHg to remove all clots from the vessels. The vessels were measured with digital paquimeter and double checked after silicon stain colored injection. All the brain arteries have the same diameter of the placenta vessels. Second part: placenta vessels from 40 human placentas that were dimensionally comparable to the sizes of appropriate cerebral vessels were isolated to create aneurysms of different shapes. The placentas were then prepared for vascular microsurgery exercises. Sylvian fissure-like dissection technique and clipping of large- and small-necked aneurysms were practiced on human placentas with and without pulsatile flow. A surgical field designed to resemble a real craniotomy was reproduced in the model. RESULTS: The human placenta has a plethora of vessels that are of the proper dimensions to allow the creation of aneurysms with dome and neck dimensions similar to those of human saccular and fusiform cerebral aneurysms. These anatomic scenarios allowed aneurysm inspection, manipulation, and clipping practice. Technical micro- surgical procedures include simulation of sylvian fissure dissection, unruptured aneurysm clipping, ruptured aneurysm clipping, and wrapping; all were reproduced with high fidelity to the haptics of live human surgery. CONCLUSION: 1) Human placenta vessels are similar to brain arteries. 2) Human placenta provides an inexpensive, widely available, convenient biological tissue that can be used to create models of cerebral aneurysms of different morphologies.